A Novel Coupler Design and Analysis with Shielding Material Tests for a CPT System of Electric Vehicles Based on Electromagnetic Resonant Coupling. (October 2019) - Duan, J; Wang, W
Abstract: In this paper, a contactless power transfer (CPT) system using a novel geometrically enhanced energy transfer coupler with three different shielding materials has been built and analysed, along with the evaluations from aspects of electromagnetics and RMS power transmitting based on electromagnetic resonant coupling. A CPT system design improvement with the proposed H-shape ferromagnetic cores and the combined semi-enclosed passive electromagnetic shielding methods have been investigated in terms of generated electromagnetic field characteristics, system power transfer ratings, system efficiency optimization and performances of shielding materials. The results have shown that, across the range of operating frequency of the CPT system, aluminium shielding as a metallic material method could deliver better overall CPT system performance than other two ferromagnetic materials, steel 1010 and ferrite. In addition, the coupler prototype design limitations, misalignment tolerance and the passive shielding design considerations including distance between windings and inner surfaces of shielding shells have been discussed.